2014
DOI: 10.1097/gme.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Long-term overall and disease-specific mortality associated with benign gynecologic surgery performed at different ages

Abstract: Objective As bilateral salpingo-oophorectomy is frequently performed with hysterectomy for nonmalignant conditions, defining health outcomes associated with benign bilateral salpingo-oophorectomy performed at different ages is critical. Methods We assessed mortality risk associated with benign total abdominal hysterectomy or bilateral salpingo-oophorectomy among 52,846 Breast Cancer Detection and Demonstration Project Follow-up Study participants. Surgery and risk factor data were ascertained via baseline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 24 publications
5
66
0
Order By: Relevance
“…Our group 13 and others 46 have found that for most women without a cancer indication, the long-term risks of bilateral oophorectomy performed before menopause are greater than the benefits; therefore, the surgery should be limited to women who have a high-risk genetic variant predisposing the patient to cancer. 3,5 However, other authors continue to argue that, in the absence of a randomized clinical trial, the evidence against prophylactic oophorectomy derived from observational studies is not sufficient to change the practice.…”
mentioning
confidence: 96%
“…Our group 13 and others 46 have found that for most women without a cancer indication, the long-term risks of bilateral oophorectomy performed before menopause are greater than the benefits; therefore, the surgery should be limited to women who have a high-risk genetic variant predisposing the patient to cancer. 3,5 However, other authors continue to argue that, in the absence of a randomized clinical trial, the evidence against prophylactic oophorectomy derived from observational studies is not sufficient to change the practice.…”
mentioning
confidence: 96%
“…In contrast, in a large prospective cohort of 25.448 women enrolled in the Women's Health Initiative Observational Study hysterectomy with salpingooophorectomy (n=14 254) was not associated with an increased risk of IHD and of total CVD [54]. Bilateral salpingo-oophorectomy increases the risk of CVD-related mortality, particularly when performed before the age of 45 years [48,55,56].…”
Section: Bilateral Salpingo-oophorectomy and Premature Cardiovascularmentioning
confidence: 90%
“…Women, who underwent BSO prior to age 55 for treatment of their malignancy and survive, have an increased risk of cardiovascular disease [49].…”
Section: Cardiovascular Healthmentioning
confidence: 99%